Peran Pengurus Pondok Pesantren dalam Penguatan Karakter Disiplin dan Tanggung Jawab Sebagai Santri Putri di Pondok Pesantren Al Mubarok Mranggen Demak - Nail Zian Aulia; Margi Wahono (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
The fact that students are still found to lack discipline and are not yet responsible for their obligations at Islamic boarding schools shows the importance of the role of administrators in strengthening the character of students. This study aims to describe the role of Islamic boarding school administrators in strengthening the character of discipline and responsibility and identify factors that support and hinder its implementation. The study used a descriptive qualitative approach conducted at the Al Mubarok Islamic Boarding School in Mranggen, Demak. The research subjects consisted of the head of the Islamic boarding school administrators, Islamic boarding school administrators, and female students who were selected purposively. Data were collected through observation, interviews, and documentation, then analyzed through data reduction, data presentation, and drawing conclusions. The validity of the data was tested using source triangulation and technical triangulation. The results of the study indicate that the strengthening of discipline and responsibility is carried out through the stages of moral knowing, moral feeling, and moral action based on Thomas Lickona's theory which is implemented through habituation, role models, supervision, evaluation, and routine Islamic boarding school activities. Supporting factors include a structured development program, collaboration among administrators, and a conducive boarding school environment. These findings indicate that the active role of administrators contributes to strengthening the students' discipline and sense of responsibility